Fluctuating solutions for the evolution of domain walls - Dutra, Alvaro de Souza [UNESP]; Correa, R. A. C. [UNESP] (Elsevier B.V., 2009)
A class of oscillating Lorentz-covariant configurations for the evolution of the domain walls in diverse dimensions are analytically obtained. It is shown that the oscillating solutions in the case of domain walls are responsible for structures which are larger than the usual kink-like configurations and, in the Lorentz-covariant evolution case, lead to long-standing configurations. (C) 2009 Elsevier B.V. All rights reserved.